Dogs with Thoracolumbar Intervertebral Disc Extrusion - Dynamic Study in Myelography - Baumhardt, Raquel; Rosa, Maurício; Vargas, Diego; Schwab, Marcelo; Wrzesinski, Mathias; Rauber, Júlia; Chaves, Julya; Mazzanti, Alexandre (Acta Scientiae Veterinariae, 2023)
Background: Myelography is recommended for diagnosing thoracolumbar intervertebral disc extrusion (IVDE) in dogs. The authors of this study found that the images of myelograms obtained in the lateral radiographic view during the injection of contrast medium contained relevant information that assisted in determining the location of spinal cord compression in dogs with IVDE; however, no studies have reported a possible contribution of these images in the diagnosis of compression. This study aimed to evaluate the contribution of radiographic views acquired during contrast injection (dynamic study) to the location of spinal cord compression in dogs with thoracolumbar IVDE. Materials, Methods & Results: Myelograms that defined extradural compression of the spinal cord in dogs with a definitive diagnosis of thoracolumbar or lumbar IVDE were included. In addition to conventional ventrodorsal, left and right oblique, and lateral radiographic views (obtained after contrast administration), lateral radiographic views acquired during the injection of at least 75% of the total calculated contrast volume in each patient (dynamic study). The examinations were evaluated by veterinary doctors, a radiologist, and a neurologist, all experienced in myelography assessments. In each radiographic view, the possibility of locating the affected intervertebral space (deviation or attenuation of the contrast column or absence of alteration) was observed. We analyzed which view, dynamic study, or conventional lateral study better demonstrated the compression site. The data were statistically analyzed. A total of 74 myelographic examinations were included in the study. Regarding the possibility of locating the affected intervertebral space in each radiographic view and the evaluators' perception of diagnostic evidence between the dynamic study and conventional lateral views, there was no statistical difference among the evaluators. Considering the total evaluations among the evaluators, the dynamic study identified the compression site in 75% of cases, while the conventional lateral view identified the compression site in 66.2%. The perceptions of the evaluators regarding the diagnostic evidence of the dynamic and conventional lateral views were 37.16% in favor of the dynamic study, 33.78% were indifferent, 8.78% in favor of the conventional lateral view, and 20.27% were not evident. There was a statistically significant difference in favor of the dynamic study for better diagnostic evidence compared to the conventional lateral view. In two patients, the dynamic study was crucial for determining the compression site, expediting the execution of decompressive surgeries and avoiding further diagnostic imaging interventions. Discussion: Myelography is an acceptable imaging modality for diagnosing IVDE in dogs when advanced imaging modalities are not available, especially in cases where dogs with severe neurological deficits need to undergo spinal decompression surgery as quickly as possible. Dynamic studies can assist in detecting ventral and dorsal compressive lesions, as well as the intervertebral space to be accessed, particularly in cases where conventional projections of the myelographic examination show subtle ventral or dorsal compressions or an extensive intramedullary pattern due to parenchymal edema, resulting in failure to fill the contrast columns for more than one intervertebral space. Considering that the dynamic study proved to be more effective in highlighting the compression site than the conventional lateral view, its inclusion in myelography examinations can contribute to improved diagnostic accuracy. In conclusion, dynamic myelography aids in determining lesion location, and its inclusion in conventional myelographic studies of dogs with suspected IVDE is recommended. Keywords: radiographic views, extradural compression, disc extrusion, spinal cord. Título: Cães com Extrusão de Disco Intervertebral Toracolombar - Estudo Dinâmico em Mielografia Descritores: projeções radiográficas, compressão extradural, extrusão de disco, medula espinhal.